Strong Association of Variants around FOXE1 and Orofacial Clefting. (April 2014) - Ludwig, K.U.; Böhmer, A.C.; Rubini, M.; Mossey, P.A.; Herms, S.; Nowak, S.; Reutter, H.; Alblas, M.A.; Lippke, B.; Barth, S.; Paredes-Zenteno, M.; Muñoz-Jimenez, S.G.; et al.
Nonsyndromic orofacial clefting (nsOFC) is a common, complex congenital disorder. The most frequent forms are nonsyndromic cleft lip with or without cleft palate (nsCL/P) and nonsyndromic cleft palate only (nsCPO). Although they are generally considered distinct entities, a recent study has implicated a region around the FOXE1 gene in both nsCL/P and nsCPO. To investigate this hypothesis, we analyzed the 2 most strongly associated markers (rs3758249 and rs4460498) in 2 independent samples of differing ethnicities: Central European (949 nsCL/P cases, 155 nsCPO cases, 1163 controls) and Mayan Mesoamerican (156 nsCL/P cases, 10 nsCPO cases, 338 controls). While highly significant associations for both single-nucleotide polymorphisms were obtained in nsCL/P (rs4460498: p Europe = 6.50 × 10 −06, p Mayan = .0151; rs3758249: p Europe = 2.41 × 10 −05, p Mayan = .0299), no association was found in nsCPO ( p > .05). Genotyping of rs4460498 in 472 independent European trios revealed significant associations for nsCL/P ( p = .016) and nsCPO ( p = .043). A meta-analysis of all data revealed a genomewide significant result for nsCL/P ( p = 1.31 × 10 −08 ), which became more significant when nsCPO cases were added ( p nsOFC = 1.56 × 10 −09 ). These results strongly support the FOXE1 locus as a risk factor for nsOFC. With the data of the initial study, there is now considerable evidence that this locus is the first conclusive risk factor shared between nsCL/P and nsCPO.